Israel's New Constitutional Imagination: The Nation State Law and Beyond. Issue 2 (November 2019) - Jamal, Amal
Abstract : The following analysis of the Israeli Nation State law reflects on the emerging new constitutional imagination in Israel. It argues that this Zionist imagination mirrors the deep sociological and political changes taking place in Israeli society. The hegemonic political elites have transformed the Israeli constitutional identity from one based on constructive legal ambiguity into one rooted in exclusive ethno-theological values. The latter stands in direct negation of the Zionist constitutional formula promoted by the founding fathers of the State as embodied in the 1948 Declaration of Independence. This rhetoric of the Declaration of Independence incorporated liberal values, in spite of the fact that the Labour Zionist political elite of the time was not fully committed to the practical meanings of these values. The current hegemonic elite in Israel views such a veiling strategy as not only unnecessary, but also as hazardous.